The Role of Transformational Leadership in Improving the Quality of Civil Servant Human Resource Development in East Kalimantan - Jerry Indrawan; Reja (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2026)
Objective: To explore the role of transformational leadership in improving the quality of human resource development of Civil Servants (ASN) across five government agencies in East Kalimantan Province. Design/Methods/Approach: This study employs a qualitative research methodology with a literature review and thematic analysis approach, synthesizing findings from various scientific literature and field case analyses. Findings: Transformational leadership serves as a crucial driving force in transforming a rigid bureaucratic mindset into a more innovative and adaptive one. Its application across various agencies (East Kalimantan Regional Legislative Council Secretariat, Energy and Mineral Resources Agency, Samarinda City Government, and Human Resources Development Agency) demonstrates performance improvement through the strengthening of organizational culture, encouragement of transparency, and acceleration of capabilities via training. Despite challenges such as resistance from a hierarchical culture, this leadership style has proven to enhance psychological empowerment, organizational commitment, and the professionalism of civil servants. Originality/Value: This research provides novelty by presenting a comprehensive synthesis of transformational leadership implementation specifically across five distinct government agencies in East Kalimantan. It offers a holistic view of how this leadership style dismantles rigid bureaucratic cultures in a rapidly developing region. Practical/Policy implication: The findings recommend the strengthening of transformational leadership within government agencies as a strategic policy to realize competent, adaptive, and high-integrity